Long-Term Overconsumption of Fat and Sugar Causes a Partially Reversible Pre-inflammatory Bowel Disease State - Arnone, Djésia; Vallier, Marie; Hergalant, Sébastien; Chabot, Caroline; Ndiaye, Ndeye Coumba; Moulin, David; Aignatoaei, Anda-Maria; Alberto, Jean-Marc; Louis, Huguette; Boulard, Olivier; Mayeur, Camille; Dreumont, Natacha; et al. (Frontiers in Nutrition, 2021)
Nutrition appears to be an important environmental factor involved in the onset of inflammatory bowel diseases (IBD) through yet poorly understood biological mechanisms. Most studies focused on fat content in high caloric diets, while refined sugars represent up to 40% of caloric intake within industrialized countries and contribute to the growing epidemics of inflammatory diseases. Herein we aim to better understand the impact of a high-fat-high-sucrose diet on intestinal homeostasis in healthy conditions and the subsequent colitis risk. We investigated the early events and the potential reversibility of high caloric diet-induced damage in mice before experimental colitis. C57BL/6 mice were fed with a high-fat or high-fat high-sucrose or control diet before experimental colitis. In healthy mice, a high-fat high-sucrose diet induces a pre-IBD state characterized by gut microbiota dysbiosis with a total depletion of bacteria belonging to Barnesiella that is associated with subclinical endoscopic lesions. An overall down-regulation of the colonic transcriptome converged with broadly decreased immune cell populations in the mesenteric lymph nodes leading to the inability to respond to tissue injury. Such in-vivo effects on microbiome and transcriptome were partially restored when returning to normal chow. Long-term consumption of diet enriched in sucrose and fat predisposes mice to colitis. This enhanced risk is preceded by gut microbiota dysbiosis and transcriptional reprogramming of colonic genes related to IBD. Importantly, diet-induced transcriptome and microbiome disturbances are partially reversible after switching back to normal chow with persistent sequelae that may contribute to IBD predisposition in the general population.